Business model analysis on Zonnebloem souvenir using the business model canvas approach in the Covid-19 pandemic - Millaningtyas, Restu; Hardaningtyas, Ratna Tri; Cahyaningrum, Yunike Adityas (Eximia, 2022)
The Covid-19 pandemic caused an economic shock, affecting the economy individually, micro, small businesses, and even globally. But excluding Zonnebloem Souvenir, its product is becoming more popular, and sales are increasing both nationally and internationally. Zonnebloem Souvenir is a creative enterprise inspired by idolizing K-Pop. Its owner decided to produce Snow Kit NCT, Crewneck, and others. The business was founded in September 2019 and used Twitter as its marketing tool. Currently, Zonnebloem Souvenir does not have a business model. By creating the appropriate business model, Zonnebloem can face the competition and grow its business. This research was conducted to map the business with a business model canvas. After that, a new business model design was produced as business development. The results of the processing state that the picture of the Zonnebloem Souvenir business model is good when viewed from the business model canvas. The SWOT analysis generates the strengths and opportunities that can be used to develop the business, and weaknesses and threats are found that must be alerted. As the result, Zonnebloem Souvenir is advised to be able to grow its business by increasing its customer segment, providing services by giving discounts, and increasing revenue by adding a variety of sales products.